DIGITAL TRANSFORMATION OF GAMIFICATION-BASED BIOLOGY EDUCATION - Dian Ratna Sari; Radho Al Kausar (BIOCHEPHY: Journal of Science Education, 2025)
The digital transformation of education signifies a fundamental shift that extends beyond the mere conversion of traditional instructional materials into digital formats. One manifestation of this shift is the development of gamified learning media, particularly within biology education. This study explores the potential of gamified digital environments to foster cognitive engagement, deepen conceptual understanding, and enhance learner motivation. Employing a research and development approach guided by the ADDIE model comprising analysis, design, development, implementation, and evaluation the media was created using the Genially platform. Implementation outcomes indicated that 64.4% of users deemed the media suitable for use, 61.5% positively rated its interactivity and user interface, and 62.3% affirmed its alignment with students’ proficiency levels and intended learning outcomes. Accordingly, the gamified learning media contributes to the diversification of biology instructional tools, promoting meaningful learning experiences and increased student engagement.